2014
DOI: 10.4103/0377-4929.138738
|View full text |Cite
|
Sign up to set email alerts
|

Genotype MTBDR plus assay for molecular detection of rifampicin and isoniazid resistance in Mycobacterium tuberculosis

Abstract: The new genotype MTBDR plus assay represents a rapid, reliable tool for the detection of MDR-TB, wherein results are obtained in 5 h allowing early and appropriate treatment, which is essential to cut the transmission path and reduce the spread of MDR-TB. The genotype MTBDR plus assay can readily be included in a routine laboratory work for the early diagnosis and control of MDR-TB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
3
2
0
Order By: Relevance
“…The most common mutation associated with rifampicin resistance was S531L mutation in the rpoB region consistent with the findings of various other studies [ 12 – 15 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The most common mutation associated with rifampicin resistance was S531L mutation in the rpoB region consistent with the findings of various other studies [ 12 – 15 ].…”
Section: Discussionsupporting
confidence: 91%
“…This study showed low rates (1%) of MDR TB among new sputum positive pulmonary TB patients similar to other Indian studies [ 9 , 10 ]. The prevalence of INH monoresistance ranging from 1% to 7% has been reported in various Indian studies [ 11 , 12 ] and our study population showed 1.5% INH monoresistance.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Most of the isolates had S315T and S531L mutations in the katG and rpoB genes, respectively. This is in line with what was observed among MDR isolates by using not only line-probe assays (69.8 vs. 55.9–90.6% for S315T katG; 64.1 vs. 41.4–67.2% for S531L rpoB ) (Farooqi et al, 2012 ; Shubladze et al, 2013 ; Sharma et al, 2014 ; Javaid et al, 2016 ; Spinato et al, 2016 ) but also sequencing strategy (66–76% for S315T katG; 46.3–66% for S531L rpoB ) (Jou et al, 2005 ; Ali et al, 2011 ; Makadia et al, 2012 ; Jagielski et al, 2015 ; Unissa et al, 2015 ). Both these mutations are thought to be low fitness cost mutations, with no adverse effect on transmission capacity (Gagneux, 2009 ).…”
Section: Discussionsupporting
confidence: 87%
“…The main difference in these latter findings may show our inclusion of all forms of presumptive tuberculosis while other studies included identified cases of Mycobacterium tuberculosis . In contrast, our finding was higher when compared with studies conducted in Metema and Armacho (5.7%) [ 7 ], Felege Hiwot Referral Hospital, and Debre Tabor Hospital (14.6%) [ 25 ], in three referral hospitals and the regional laboratory in Addis Ababa (15.11%) [ 26 ], other parts of Ethiopia (4.7–10.8%) [ 27 29 ], Nigeria (10.3%) [ 30 ] and India (2.31%) [ 31 ]. The variations might be due to the difference in study design, type and number of participants, and environmental conditions.…”
Section: Discussionmentioning
confidence: 99%